Detection of autologous blood transfusions using a novel dried blood spot method. Issue 11 (27th November 2017) - Cox, Holly D.; Miller, Geoffrey D.; Lai, Auriella; Cushman, Dan; Eichner, Daniel
Abstract : In doping control laboratories, autologous blood transfusions are currently detected using an indirect method that monitors changes in an athlete's hemoglobin concentration [Hb] and reticulocyte percent (Ret%) over time. The method is limited by the need for a phlebotomist to collect venous blood and the limited blood stability which requires temperature‐controlled shipment and analysis within 72 hours. These limitations significantly reduce the number of samples collected from each athlete and thus the utility of the method. We have recently developed a method to measure immature reticulocytes (IRC) and red blood cells (RBC) in dried blood spots, which could replace the current venous blood method. In the DBS method, cell‐specific proteins are digested with trypsin and measured by mass spectrometry. Two proteins, CD71 and Band3, are measured to count IRC and RBC, respectively. The method was tested in an autologous transfusion study consisting of 15 subjects who received blood and 11 subjects who received saline. After transfusion, the average CD71/Band3 ratio in the blood group was statistically different from the saline group at days 5, 6, 13, and 20. The average CD71/Band3 ratio decreased to a minimum of 61 ± 8% of baseline, while Ret% decreased to 75 ± 5% of baseline. Based on experimentally defined criteria, the CD71/Band3 ratio could detect 7 out of 10 blood transfusion subjects, while Ret% could detect 3 out of 10. Thus, the DBS method could improve detection of autologous transfusion and allow increased sample collection. Abstract : A method was developed to count blood cells, immature reticulocytes and red blood cells, in dried blood spots. The method was tested for detection of autologous blood transfusions and compared to the current athlete biological passport method.